Removal of Pb2+ and Cd2+ ions from aqueous solutions using guanidine modified hydrogels - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; DENİZ, SABAHATTİN (WILEY-BLACKWELL, 2011)
In this study, experimental measurements have been made on the batch adsorption of cadmium and lead ions from aqueous solutions using poly(guanidine modified 2-acrylamido-2-methylpropan sulfonic acid/acrylic acid/N-vinylpyrrolidone/2-Hydroxyethyl methacrylate), P(AMPSG/AAc/NVP/HEMA) hydrogels. The guanidyl end group bearing AMPSG monomer was synthesized from the reaction of AMPS and guanidine. The hydrogels were prepared by UV-curing technique. The morphology of the dry H10-hydrogel sample was examined by SEM. The influence of the uptake conditions, such as pH, functional monomer per cent, contact time, initial feed concentration, and foreign metal ions on the metal ion binding capacity of hydrogel, was also tested. The selectivity of the hydrogel toward the different metal ions tested was Hg(II) > Pb(II) > Au(III) > Cd(II). The adsorption isotherm models were applied to the experimental data, and it was seen that the Langmuir isotherm model was the best fit for the adsorption of Cd(II) and Pb(II) ions on P(AMPSG/AAc/NVP/HEMA) hydrogel. It was found that adsorbed lead and cadmium ions on P(AMPSG/AAc/NVP/HEMA) hydrogel can be effectively desorbed by acid leaching and the regenerated P(AMPSG/AAc/NVP/HEMA) hydrogel can be reused almost five times less without any loss of adsorption capacity. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: hydrogel; metal uptake; guanidine; UV-curing; heavy metal; METAL-IONS; SORPTION PROPERTIES; ANION-EXCHANGERS; ACTIVATED CARBON; ADSORPTION; COMPLEXATION; LIGANDS; DYE